2023
DOI: 10.52700/assap.v4i1.229
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Factor Affecting Non-Performing Loans (NPLs): Evidence from Commercial Bank in Pakistan Based ARDL Cointegration Approach

Abstract: The main objective of this study is to measure the NPLS in Pakistan’s commercial bank. The macroeconomic factor of Country GDP, corruption, unemployment, political instability and inflation it’s nettle the level of NPLS in commercial bank in Pakistan.  The unemployment, increasing of interest rate, low economic growth and money laundering they elaborate the changing in NPLS. high inflation, unemployment ratio, huge cases of corruption, political instability are faced by the country.we are working time series d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…However, it does not necessarily require a low FDR value, because a low FDR condition causes banking. This finding is in line with the findings of previous researchers (Azmi et al, 2023;Ikhsan & Karyatni, 2023;Print et al, 2023;Umaternate & Mongid, 2023;Zhang, 2022).…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…However, it does not necessarily require a low FDR value, because a low FDR condition causes banking. This finding is in line with the findings of previous researchers (Azmi et al, 2023;Ikhsan & Karyatni, 2023;Print et al, 2023;Umaternate & Mongid, 2023;Zhang, 2022).…”
Section: Resultssupporting
confidence: 94%
“…In addition, for banks, digitization can provide more accurate information related to customers' financial conditions (Idawati & Syafputri, 2022), so that they can mitigate the risk of non-performing financing earlier and better, as well as more efficiently and effectively. This research found that the increasingly rapid development of digitization can reduce Nonperforming Financing (NPF) in Islamic commercial banks in Indonesia, as in previous studies (Ilmiah & Islam, 2023;Lei & Li, 2021;Limited, 2022;Print et al, 2023;Sherif, 2023;Sudirman et al, 2023;Synatrya, 2021;Wu et al, 2023;Xu et al, 2022). Furthermore, digitalization is of course capable of providing significant risks if it goes hand in hand with the development of cybercrime in the future.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations